Respuesta :
Answer: FIRST OPTION
Step-by-step explanation:
You must keep on mind that, according the exponents properties, when you multiply two powers with equal base, you must add the exponents.
Then:
- Apply the distributive property as you can see below:
[tex](x*x^2)-(x*2x)-(x*3)-(4*x^2)+(4*2x)+(4*3)=x^3-2x^2-3x-4x^2+8x+12[/tex]
-Add like terms, then you obtain:
[tex]x^3-2x^2-3x-4x^2+8x+12\\x^3-6x^2+5x+12[/tex]
Answer:
A.) x3 - 6x2 + 5x + 12
Step-by-step explanation:
FOIL (First, Outer, Inner, Last)
(x-4)(x2-2x-3)
Distribute the x to everything in the other parentheses
x * x2 = x3 x * -2x = -2x^2 x * -3 = -3x
Distribute the -4 to everything in the other parentheses
-4 * x2 = -4x^2 -4 * -2x = 8x -4 * -3 = 12
Combine like terms
x3 + -2x^2 - 3x - 4x^2 + 8x + 12
x3 - 6x2 + 5x + 12